2020
DOI: 10.3389/fpsyg.2020.01159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trunk Motion, Touch, and Articulation on Upper-Limb Velocities and on Joint Contribution to Endpoint Velocities During the Production of Loud Piano Tones

Abstract: Trunk-Motion, Touch, and Articulation in Piano Performance contributed to creating forward linear velocities at the upper limb. The reported findings have implications for the performance, teaching, and research domains since they provide evidence of how pianists' trunk motion can actively contribute to the sound production and might not only be associated with either postural or expressive features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Regardless of anthropometry, the trunk orients body position for all motor behaviors ( Magill & Anderson, 2017 ). During piano performance, changes in trunk angle (COG position) has a concomitant effect on arm movement ( Verdugo et al., 2020 ). Manipulation of trunk and arm angles determines hand-keyboard orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of anthropometry, the trunk orients body position for all motor behaviors ( Magill & Anderson, 2017 ). During piano performance, changes in trunk angle (COG position) has a concomitant effect on arm movement ( Verdugo et al., 2020 ). Manipulation of trunk and arm angles determines hand-keyboard orientation.…”
Section: Discussionmentioning
confidence: 99%
“…For improving piano performance, most biomechanical and motor behavior research to date has employed protocols that emphasize reductionistic keystroke exercises ( Furuya & Kinoshita, 2008 ; Degrave et al., 2020 ; Oku & Furuya, 2017 ; Verdugo et al., 2020 ). Some have used scales, which are mechanical exercises designed to develop a pianist’s technique ( Ferrario et al., 2007 ; van Vugt et al., 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the comparison of keystrokes by professional pianists and novice pianists have shown that the control and organization of complex multi-joint motor action are influenced by long-term extensive training from an early age [74,[78][79][80][81][82][83]. Professional pianists work to reduce muscle load and achieve the physiological efficiency of fatigue-prone muscle by using more proximal joints and gravity, inter-segment, and reaction forces than novice piano players [43,84,85]. In addition, professional pianists have a smaller increase in co-activation of hand and finger muscles than amateurs and less stiffness with tempo, and the use of elbow motions allow fingertipkey contact with low stiffness across a wide range of tempi [74,86].…”
Section: Plos Onementioning
confidence: 99%
“…biorbd was used in most of the project of the Laboratoire de Simulation et Modélisation du Mouvement (S2M); particularly in analysis settings (Desmyttere et al, 2020;Jackson et al, 2012;Verdugo et al, 2020) and simulation settings (Bélaise et al, 2018;Moissenet et al, 2019) for a wide variety of movements (walking, piano playing, upper limb maximal exertions, etc.) More recently, an optimal control framework for biomechanics (bioptim, based on Ipopt (Wächter & Biegler, 2006) and ACADOS (Verschueren et al, 2019) was developed around biorbd.…”
Section: Previous Usage Of Biorbdmentioning
confidence: 99%